Opposite relations of epicardial adipose tissue to left atrial size in paroxysmal and permanent atrial fibrillation. (September 2018) - Psychari, Stavroula N; Tsoukalas, Dionysios; Varvarousis, Dimitrios; Papaspyropoulos, Anastasios; Gkika, Eleni; Kotsakis, Athanasios; Paraskevaidis, Ioannis A; Iliodromitis, Efstathios K
Objectives: Atrial fibrillation has been associated with obesity in epidemiological studies. Epicardial adipose tissue is an ectopic fat depot in the proximity of atria, with endocrine and inflammatory properties that is implicated in the pathophysiology of atrial fibrillation. Inflammation also has a role in atrial arrhythmogenesis. The aim of this study was to investigate the potential relations of epicardial adipose tissue to left atrial size and to adiponectin and the pro-inflammatory mediators, high-sensitivity C-reactive protein, and interleukin-6 in paroxysmal and permanent atrial fibrillation. Methods: This was a cross-sectional study of 103 atrial fibrillation patients, divided into two subgroups of paroxysmal and permanent atrial fibrillation, and 81 controls, in sinus rhythm. Echocardiography was used for estimation of epicardial adipose tissue and left atrial size and high-sensitivity C-reactive protein, interleukin-6 and adiponectin were measured in all subjects. Results: Atrial fibrillation patients had significantly larger epicardial adipose tissue compared with controls (0.43 ± 0.17 vs 0.34 ± 0.17 cm, p = 0.002). Atrial fibrillation presence was independently related to epicardial adipose tissue thickness ( b = 0.09, p = 0.002). Opposite associations of epicardial adipose tissue with left atrial volume existed in atrial fibrillation subgroups; in the paroxysmal subgroup, epicardial adipose tissue was directly related to left atrial volume ( R = 0.3, p = 0.03), but in the permanent one the relation was inverse ( R = −0.7, p < 0.0001). Adiponectin, high-sensitivity C-reactive protein and interleukin-6 were elevated in both atrial fibrillation groups. Only interleukin-6 was related to epicardial adipose tissue size. Conclusion: Opposite associations of epicardial adipose tissue with left atrial size in paroxysmal and permanent Atrial fibrillation and elevated inflammatory markers, suggest a role of epicardial adipose tissue and inflammation in the fibrotic and remodeling process.